KONSTRUKSI LAPORAN KASUS PANAMA PAPERS PADA INVESTIGASI TEMPO.CO 04 APRIL 2016 - Puspa Warni, Komang Ayu; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2018)
ABSTRACT The power of the media is found on the fact that media can be the main source of ideas and opinions. This study aims to found out how Tempo.co construct the facts that received in the field to be an investigative report and published on April 4, 2016. Researchers used two theories to support the research process. Among them is the theory of Agenda setting used in assessing the processing of facts, and the next theories is Framing theory model by Robert N. Entman. The type of research used is qualitative with constructivist paradigm. The results of this study, the construction of an investigative report made by Tempo.co. It is judged from the selection of issues and assertion aspects. The issue that Tempo.co wants to highlight through this investigative report is the involvement of prominent figures from various countries in the world, the practice of tax evasion in large scale and the appear of public figures from Indonesia in the leaked Mossack Fonseca documents. The highlighted aspects are tax evasion, money laundering, major crimes, massive scams, the involvement of prominent figures, conceal facts, and improper tactics.   Keyword : Framing Analysis, Online News, Tax Evation, Panama Pappers, Tempo.co